2011
DOI: 10.1029/2011gl048717
|View full text |Cite
|
Sign up to set email alerts
|

Responses of marine ecosystem to typhoon passages in the western subtropical North Pacific

Abstract: Strong phytoplankton blooms are occasionally observed around a recurvature point of typhoon tracks in the western subtropical Pacific. These are noteworthy events in subtropical regions where both nutrient concentrations and biological production are persistently low. We investigated the response of phytoplankton to typhoon passage using a numerical model with/without biogeochemical processes. The model reproduced the observed patch‐like phytoplankton bloom around a recurvature point of Typhoon Keith in 1997. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…S2f). This differs from the traditional method of composite for anecdotal events67891112131415, which fixes the calendar period instead, yielding different duration times after TC-passage for different locations. We repeat the procedure for each TC and then average over all of them.…”
Section: Methodsmentioning
confidence: 97%
“…S2f). This differs from the traditional method of composite for anecdotal events67891112131415, which fixes the calendar period instead, yielding different duration times after TC-passage for different locations. We repeat the procedure for each TC and then average over all of them.…”
Section: Methodsmentioning
confidence: 97%
“…Shibano et al . [] showed that without biogeochemical processes, the increase in Chl a in a numerical model was much smaller than observation, indicating that the biogeochemical processes are essential factors related to surface phytoplankton increases. However, they did not quantify the contributions of physical and biogeochemical processes to the increases in the surface phytoplankton.…”
Section: Introductionmentioning
confidence: 99%
“…Our goal here is to explain the mechanisms that lead to the bloom asymmetry through idealized biophysical model experiments. Previous model studies examined specific responses under realistic [ Liu et al ., ; Zheng et al ., ; Chiang et al ., ] or idealized [ Shibano et al ., ] regional setting, at grid sizes ranging from 6.25 km [ Chiang et al ., ] to 25 km [ Zheng et al ., ]; except Price et al . [] which was a process study using a 15 km grid.…”
Section: Introductionmentioning
confidence: 99%